2014
DOI: 10.1039/c4gc00092g
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of ionic liquid-spun chitin fibers for the extraction of uranium from seawater: seeking the strength of chitin and the chemical functionality of chitosan

Abstract: A platform was developed for the surface modification of ionic liquid-spun chitin fibers, that provides the physical properties of chitin with chitosan's functional properties on the surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
83
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(84 citation statements)
references
References 33 publications
1
83
0
Order By: Relevance
“…Among these methods, development of uranium adsorption materials containing the amidoxime functional group has the highest potential because of its high chelating affinity and selectivity toward uranium. [1d,7] Amidoxime groups are mainly generated by treating the nitrile group with hydroxylamine . Amidoxime groups have been displayed on a variety of supporting materials (such as polymeric fibers, porous polymers, magnetic microspheres, hydrogels, and metal organic frameworks) and exhibit excellent specificity and capacity for uranium sequestration.…”
Section: Introductionmentioning
confidence: 99%
“…Among these methods, development of uranium adsorption materials containing the amidoxime functional group has the highest potential because of its high chelating affinity and selectivity toward uranium. [1d,7] Amidoxime groups are mainly generated by treating the nitrile group with hydroxylamine . Amidoxime groups have been displayed on a variety of supporting materials (such as polymeric fibers, porous polymers, magnetic microspheres, hydrogels, and metal organic frameworks) and exhibit excellent specificity and capacity for uranium sequestration.…”
Section: Introductionmentioning
confidence: 99%
“…Another objective of the presentw ork was to study the properties of ionic liquids, as they have been shown to have potentiala pplicationsi nv ariousf ields including electrochemistry, [29,30] catalysts, [31] synthesis, [32,33] and separation, [34,35] both as solvents/media and as reactants. In this work, the ionic liquid selected was 1-ethyl-3-methylimidazoliumb is(trifluoromethylsulfonyl)imide ([Emim][Tf 2 N]), which has prospects for application in electrochemistry and its conductivity is comparable to that of the best organic electrolyte solutions.…”
Section: Introductionmentioning
confidence: 99%
“…10 The high capacity absorbance of chitin bers functionalized with a uranyl-selective amidoxime group used for the extraction of uranium from seawater has been reported. 11 The hydrophobic of the modied chitin surface leads to the highly effective separation of oil from water. 12 An amphiphilic chitosan surface has been achieved by graing hydrophilic polyacrylamide and hydrophobic polystyrene to allow reversible switching in polar and non-polar media.…”
Section: Introductionmentioning
confidence: 99%